If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 9 = 15x + -3 Reorder the terms: 9 + 9x = 15x + -3 Reorder the terms: 9 + 9x = -3 + 15x Solving 9 + 9x = -3 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 9 + 9x + -15x = -3 + 15x + -15x Combine like terms: 9x + -15x = -6x 9 + -6x = -3 + 15x + -15x Combine like terms: 15x + -15x = 0 9 + -6x = -3 + 0 9 + -6x = -3 Add '-9' to each side of the equation. 9 + -9 + -6x = -3 + -9 Combine like terms: 9 + -9 = 0 0 + -6x = -3 + -9 -6x = -3 + -9 Combine like terms: -3 + -9 = -12 -6x = -12 Divide each side by '-6'. x = 2 Simplifying x = 2
| h(t)=4t^2+4t+1 | | 4(2-x)+1=2x+2-5(1-4x) | | 5k+4=10-k | | 5(6a+8)=29+7a | | [5-9]-[12]= | | 2(x^2+2x)=390 | | cos(x/4)=0 | | 300[4]= | | 13x+2=15x-6 | | Y*7=9 | | U=4-3x | | 4(3+x)=52 | | 8n-3=6n-2 | | 6.11x+36=37.3321+6x | | (-6x+5)-(x^2+x-9)= | | Y-17=-11 | | 5(6a+8)=-29+7 | | -7=8+-50+X | | X-12.75=29.75 | | 5a+8=13 | | [-6+9]= | | -16=14-17x | | Log(3x)-4=-3 | | 2e-12=7e+18 | | Log(3c)-4=-3 | | x^2+4x-75=0 | | b+4a=17 | | (5+y)+a=a+5 | | -34=-16+a | | 180=4x+11x+19 | | (4x+2)-(-6x+9)= | | 3.50x+5.00y=97.50 |